Pengaruh Intellectual Capital dan Opini Audit terhadap Return Saham - Riskihanty DS, Fhanesa Nur; Farida, Yusriyati Nur (Jurnal Riset Akuntansi Soedirman, 2025)
This study aims to examine and analyze the effect of Intellectual Capital and audit opinion on stock return in banking companies listed on the Indonesia Stock Exchange in 2019-2022. Signalling theory was used as the basis for this study. The type of data used is secondary data in the form of annual reports and audited financial statements. The sample used in this study was 126 research data from 41 companies with a research period of four years. The sampling technique used is a purposive sampling technique based on certain criteria. The data analysis techniques used in this study are classical assumption tests, outlier tests, multiple linear regression analysis, determination coefficient tests, goodness of fit tests, and hypothesis testing. The results of this study show that: (1) Intellectual Capital has a positive effect on stock return. (2) Audit opinion has no positive effect on stock return. The implications of the study's conclusion are that it is expected to help banking companies in increasing stock return by paying attention to the factors that influence it so that it can maintain investor confidence to continue investing and can be used as a reference for further study related to stock return.